Preparation of Dyeing Prescription and Investigation of Natural Hair Dyeing Properties of Walnut (Juglans regia L.), Logwood (Alnus glutinosa L.), Alkanet (Alkanna tinctoria L.) Madder red (Rubai tinctorum L.) and Wouw (Re - Onal, Adem; Demir, Birnur (Asian Journal of Chemistry, 2010)
In this work, the root of madder red (Rubia tinctorum L.), leaves of logwood (Alnus glutinosa L.), coco and leaves of walnut (Juglans regia L.), seeds and leaves of wouw (Reseda luteola L) were extracted in deinoized water after dried and bindered. These solutions were used portion of 100 mL and various transtion element's salts were added (FeSO4, CoCl2, KAlSO4·12H2O, AgNO3). Each of them evaporated to 50 mL and 1 mL of almond oil was added into each of samples. Human hears prepareted before, by adding to this dye pat, the dyeing time was determined. According to the this results, for madder red-CoCl2 5.3 h and chestnood clour; for wouw-KAlSO4·12H2O 6 h and rofle yellow; for walnut-KAlSO4·12H2O 6 h, FeSO4 6 h and pale chestnood, for madder red-CoCl2 6 h and redhead; for common alder walnut-FeSO4 7.5 h and dark chestnood; for walnut-FeSO4 8.30 h and dark chestnood; for common alder-walnut - FeSO4 8 h and black;for walnut- FeSO4 6.3 h and nut shell. Same dyeings were made for each samples in oven at 40 ºC and dyeing periods were determined as 4, 3.45, 2.40, 2, 2.30, 3.50, 2.50, 3.25 h, respectively.